Comparison of vector competence of Aedes mediovittatus and Aedes aegypti for dengue virus: implications for dengue control in the Caribbean. - B Katherine Poole-Smith; Ryan R Hemme; Mark Delorey; Gilberto Felix; Andrea L Gonzalez; Manuel Amador; Elizabeth A Hunsperger; Roberto Barrera (Public Library of Science (PLoS), 2015)
Aedes mediovittatus mosquitoes are found throughout the Greater Antilles in the Caribbean and often share the same larval habitats with Ae. Aegypti, the primary vector for dengue virus (DENV). Implementation of vector control measures to control dengue that specifically target Ae. Aegypti may not control DENV transmission in Puerto Rico (PR). Even if Ae. Aegypti is eliminated or DENV refractory mosquitoes are released, DENV transmission may not cease when other competent mosquito species like Ae. Mediovittatus are present. To compare vector competence of Ae. Mediovittatus and Ae. Aegypti mosquitoes, we studied relative infection and transmission rates for all four DENV serotypes.To compare the vector competence of Ae. Mediovittatus and Ae. Aegypti, mosquitoes were exposed to DENV 1-4 per os at viral titers of 5-6 logs plaque-forming unit (pfu) equivalents. At 14 days post infectious bloodmeal, viral RNA was extracted and tested by qRT-PCR to determine infection and transmission rates. Infection and transmission rates were analyzed with a generalized linear model assuming a binomial distribution.Ae. Aegypti had significantly higher DENV-4 infection and transmission rates than Ae. mediovittatus.This study determined that Ae. Mediovittatus is a competent DENV vector. Therefore dengue prevention programs in PR and the Caribbean should consider both Ae. Mediovittatus and Ae. Aegypti mosquitoes in their vector control programs.